Enhancing knowledge and critical thinking about health through biology instruction based on the health belief model among secondary school students - Izza, Jasmine Nurul; Suwono, Hadi (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Health and well-being are paramount objectives within the Sustainable Development Goals (SDGs). Numerous health challenges endure due to insufficient early health teaching in educational institutions. Nonetheless, scant research has amalgamated school-based education with essential health principles. This study aimed to examine the effect of problem-based learning (PBL) based on the health belief model (HBM), also referred to as HB-PBL, on students’ learning outcomes and critical thinking skills. The type of research is a quasi-experimental design featuring a pre-test and post-test with a non-equivalent control group. The sample was 70 12th-grade science students at SMAN 3 Malang, Indonesia. Students participated in cooperative problem-solving centered on human heredity and inherited disorders. Instrument research is a type of exam that consists of multiple-choice questions and an essay. The data obtained were analyzed using analysis of covariance (ANCOVA) at a 95% confidence level. ANCOVA results showed that the instructional method had a significant effect on both learning outcomes and critical thinking skills, with a significance value below 0.05 (p < 0.05). This study demonstrated that HB-PBL significantly improves students’ learning outcomes and critical thinking skills by fostering greater engagement with health-related issues. Subsequent research ought to examine the impact of health attitudes on students' learning behaviors.